A nanotree-like WO3 film with adjustable defect concentration and its photocatalytic activity. (1st June 2021) - Hu, Yifei; Ping, Xuecheng; Zhang, Yan; Hao, Liang; Liu, Tongyang; Zhao, Qian; Lu, Yun; Liu, Jizi
Abstract: A nanotree-like WO3 film with a large specific surface area was prepared by the facile hydrothermal process. During the procedure, a hexagonal/monoclinic mixed WO3 was formed, and the prepared WO3 crystals contained some defects, including W 5+ and oxygen vacancies. To induce more defects, we further performed a mild solution reduction in the solution of EG + NH4 F at a relatively low temperature of 333 K. The reduction treatment did not change the surface morphology of the WO3 film. However, the defect concentration first increased and then declined with the reduction time from 0 to 96 h. A proper defect concentration is beneficial for improving the photocatalytic activity of WO3 film, while excessive defects decreased photocatalytic activity instead. A volcano-like relationship between the photocatalytic activity and the defect concentration was also demonstrated. Compared with the as-annealed WO3 film, the photocatalytic activity of the as-reduced WO3 film for 48 h increased to 2.1 times. The hydrothermal process, followed by a mild solution reduction, is an effective way to prepare WO3 film with high photocatalytic activity. Graphical abstract: Image 1 Highlights: Low temperature reduction in EG + NH4 F induced oxygen vacancies and W 5+ in WO3 film. Defect concentration could be adjusted by changing the reduction time. A volcano-like relationship between defect concentration and PC activity was set up. PC activity was increased to 2.1 times by defect concentration regulation.